Pemahaman Masyarakat Subulussalam Kota Terhadap Surah Al-Hujurāt Ayat 13 Dalam Kaitannya Dengan Ta’aruf Pra Nikah - Boihaqi bin Adnan; Cut Riswana Warlita (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2025)
This study aims to explore the understanding of the people of Subulussalam City regarding Surah Al-Ḥujurāt verse 13, particularly in relation to ta’aruf before marriage. Ta’aruf refers to the initial process undertaken by prospective couples—male and female—to get to know each other, so that their forthcoming marriage is based on mutual understanding and informed decision-making. The research employs a descriptive qualitative method, with data collected through observation and interviews. The data were analyzed through the stages of data collection, data reduction, and conclusion drawing. The findings of the study are as follows:In the translation category, 3 informants were classified as having a good understanding, while 1 informant was found to have no understanding. In the interpretation category, 2 informants demonstrated a good understanding, while 4 were categorized as having only partial understanding. In the extrapolation category, 6 informants were found to have a good understanding, while 2 informants showed no understanding.